Progress in diagnosis and therapy of gastrointestinal diseases - Rydzewska, Grażyna (Przewodnik Lekarza/Guide for GPs, 2008)
This review summarizes recent progress in diagnosis and treatment of gastrointestinal diseases. New techniques – double-balloon enteroscopy and capsule endoscopy for small bowel diagnosis, capsule endoscopy for oesophageal and colon diseases, transnasal endoscopy, and intragastric balloon for obesity treatment – have been described. New imaging endoscopic technologies including magnification endoscopy, narrow band imaging, Fujinon intelligent chromoendoscopy and laser confocal endomicroscopy, have been introduced. Progress has also been made in several areas in the treatment of gastrointestinal diseases, including eradication therapy for Helicobacter pylori, probiotics use, biological treatment for IBD and new possibilities of pancreatic cancer treatment.